2004
DOI: 10.2172/828261
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Tritium Surface Distribution on TFTR Bumper Limiter Tiles

Abstract: The tritium surface distribution on graphite tiles used in the TFTR bumper limiter and exposed to TFTR D-T discharges from 1993 to 1997 was measured by the Tritium Imaging Plate Technique (TIPT). The TFTR bumper limiter shows both re-/co-deposition and erosion. The tritium images for all tiles measured are strongly correlated with erosion and deposition patterns, and long-term tritium retention was found in the re-/co-depositions and flakes.The CFC tiles located at erosion dominated areas clearly showed their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Although the TF ripple is lower at the high field side than at the low-field side, higher energy triton can escape into the high field side depending on the birth point and the ripple well shape. In the case of JT-60U, the highest tritium inventory on the inner wall was observed around mid-plane, agreeing with the numerical expectation [7]. The distribution observed on the central column of ASDEX Upgrade is thus attributed to the implantation of the energetic tritons with the energy of more than 100 keV by the ripple loss and/or orbital loss as the case of JT-60U.…”
Section: Divertor Regionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the TF ripple is lower at the high field side than at the low-field side, higher energy triton can escape into the high field side depending on the birth point and the ripple well shape. In the case of JT-60U, the highest tritium inventory on the inner wall was observed around mid-plane, agreeing with the numerical expectation [7]. The distribution observed on the central column of ASDEX Upgrade is thus attributed to the implantation of the energetic tritons with the energy of more than 100 keV by the ripple loss and/or orbital loss as the case of JT-60U.…”
Section: Divertor Regionsupporting
confidence: 84%
“…In D-T discharge machines like JET and TFTR [1][2][3][4], tritium mainly co-deposited with eroded first wall material (carbon). In D-D discharge machines, on the other hand, according to our recent studies, tritium distribution on the plasma-facing wall well corresponded to the distribution of high energetic triton implantation [5][6][7].…”
Section: Introductionmentioning
confidence: 94%
“…Therefore it is a very important issue to evaluate retention characteristics of hydrogen isotopes (T, D, H) in in-vessel components of current plasma devices [1][2][3][4][5][6]. We have been studying the retention of hydrogen isotopes in plasma facing graphite tiles exposed to both deuterium and hydrogen discharges in JT-60U by using various methods under the joint research between Japanese universities and JAERI [7][8][9][10]. We have found that most of tritium produced by the D-D reactions was implanted into depth of micrometer range, and tritium areal distribution was independent of carbon deposition profiles, while H and D seem to be co-deposited with carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen isotope behavior in the tiles during the inner side pumping have been investigated by the tritium imaging plate technique [6][7][8][9], secondary ion mass spectroscopy (SIMS), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) [10][11][12]. These studies demonstrated that tritium, due to its high energy origin, was implanted rather deep by the orbital loss and ripple loss mechanisms [6][7][8][9], while hydrogen/deuterium profiles in divertor areas were complicated and very much influenced by surface temperature and erosion/deposition [10,11,13].…”
Section: Introductionmentioning
confidence: 99%